The genus Holaptilon Beier, 1964: discussion on the poorly known boxer mantis genus, with a new species (Mantodea, Gonypetidae) - Yilmaz, Kaan; Sevgi̇li̇, Hasan (Zootaxa, 2023)
The boxer mantis genus Holaptilon Beier, 1964 (Mantodea: Gonypetidae: Gonypetinae) is known to include two flightless species with a similar body size and morphology. Type species of the genus, H. pusillulum Beier, 1964, is reported from Israel and Jordan. An interesting species of the genus was recently identified from Iran (H. brevipugilis Kolnegari, 2018). In this research, a new species of H. yagmur Yılmaz & Sevgili sp. n. is described from Turkey. This new species was collected from Karacadağ (Şanlıurfa), a volcanic mountain in the Southeastern Anatolia region. Its typical habitat is steppic stony areas. It indicates that the species may be cryptic or nocturnal since it was collected from under stones and ground traps. This finding indicates that the genus is more widespread than previously known and may have more species yet to be discovered. The existence of the genus Holaptilon was reported for the first time in Turkey. Meanwhile, while reviewing the praying mantis list of Turkey, we determined that the samples collected from Ağrı, which are given in the Mantodea list of Turkey, were misdiagnosed as Armene robusta Mishchenko, 1956 and actually belong to the genus Holaptilon, and that Turkey currently hosts 20 praying mantis species/subspecies.